ANALISIS KEKAYAAN ASPEK FINANSIAL INVESTASI,PENINGKATAN KAPASITAS PRODUKSI PANEL PT.X DENGAN PENDEKATAN SIMULASI - Widiastuti, Dini
Abstract: In the way to the better economic and political situation in Indonesia, global competition tendencies, and wide opened opportunity for expanding market share has given a chance for PT. X to increase its panel production. The chance will need a large amount of investment and the feasibility study will be needed in order to calculate the investment\'s risk. The feasibility in this matter is based on financial aspect, which is the rate of return and investment risk (the variability of returns from those that are expected). The criteria for decision making is the Internal Rate of Return (IRR), and generated by simulations. Investment is feasible if the average IRR generated by simulations overcome the minimum average rate of return given. Risk in this study is identified by the probability of failure, that is the occurences of IRR less than minimum average rate of return given. To make the simulation model, identification of risk factors is made. This study has identified 12 risk factors and its characteristics. The outcome of this simulation is : lowest IRR -12.64%, highest IRR 100.77%, average IRR 32.12%, standard deviation 25.80%. The average IRR is higher than the rate of return expected, which made this investment feasible. Whereas the probability of failure for this investment is 21.19%.